Identification and characterization of cancer cells that initiate metastases to the brain and other organs - Bergmeister-Berghoff, Anna Sophie; Liao, Yunxiang; Karreman, Matthia A.; Ilhan-Mutlu, Ayseguel; Gunkel, Katharina; Sprick, Martin; Eisen, Christian; Keßler, Tobias; Osswald, Matthias; Wünsche, Susanne; Feinauer, Manuel; Gril, Brunhilde; et al. (Molecular cancer research, 2021)
Specific biological properties of those circulating cancer cells that are the origin of brain metastases (BM) are not well understood. Here, single circulating breast cancer cells were fate-tracked during all steps of the brain metastatic cascade in mice after intracardial injection over weeks. A novel in vivo two-photon microscopy methodology was developed that allowed to determine the specific cellular and molecular features of breast cancer cells that homed in the brain, extravasated, and successfully established a brain macrometastasis. Those BM-initiating breast cancer cells (BMIC) were mainly originating from a slow-cycling subpopulation that included only 16% to 20% of all circulating cancer cells. BMICs showed enrichment of various markers of cellular stemness. As a proof of principle for the principal usefulness of this approach, expression profiling of BMICs versus non-BMICs was performed, which revealed upregulation of NDRG1 in the slow-cycling BMIC subpopulation in one BM model. Here, BM development was completely suppressed when NDRG1 expression was downregulated. In accordance, in primary human breast cancer, NDRG1 expression was heterogeneous, and high NDRG1 expression was associated with shorter metastasis-free survival. In conclusion, our data identify temporary slow-cycling breast cancer cells as the dominant source of brain and other metastases and demonstrates that this can lead to better understanding of BMIC-relevant pathways, including potential new approaches to prevent BM in patients. - Implications: Cancer cells responsible for successful brain metastasis outgrowth are slow cycling and harbor stemness features. The molecular characteristics of these metastasis-initiating cells can be studied using intravital microscopy technology.
Gesehen am 09.06.2021
First published: December 22, 2020